Degrading action of floods: Damage analysis in historic buildings of the Bairro do Recife (PE) - Santos, Júlia Oliveira dos; Silva, Joyce Ketlly Soares da; Rocha, Eudes de Arimatéa; Valadares, Pedro Henrique Cabral; Soares, Willames de Albuquerque (National Journal of City Management, 2025)
Objective – Analyze the relationship between environmental events and the deterioration of historical materials due to moisture in the Bairro do Recife (PE), proposing adaptive preservation strategies. Methodology – Qualitative study based on documentary analysis, bibliographic review, and field surveys in six historical buildings. Originality/Relevance – Investigates the climate vulnerability of cultural heritage in consolidated urban areas, a topic still scarcely explored. Results – Identified a high susceptibility of local traditional materials to moisture and salinity, considering imminent risks due to geographic location and sea level rise, demanding specific preservation and maintenance interventions. Theoretical/Methodological Contributions – Proposes synthesized and targeted guidelines for sustainable adaptive actions, compatible with historical construction methods, preserving building authenticity. Social and Environmental Contributions – Encourages public partnerships to promote awareness regarding the preservation of built heritage, especially in non-listed buildings, strengthening cultural identity and environmental sustainability.